The Number of Independent Signals in Body Surface Maps - Hoekema, R.; Uijen, G.; van Oosterom, A. (Methods of Information in Medicine, 1999)
This paper reports on the number of independent signals in body surface maps measured using a variety of lead systems incorporating 32 up to 219 leads. The number of independent signals is estimated using the minimum description length. It is found that the number of independent signals in body surface maps is of the order of 10. For lead systems incorporating many leads the number of independent signals is only marginally larger than in lead systems incorporating fewer leads. A lead system incorporating 64 leads will suffice for most applications.
Keywords: Body-Surface Mapping; Lead Systems; Signal Estimation